Cervical selective nerve root block: three-dimensional puncture planning with dyna-CT is superior to conventional CT-guidance in an ex vivo model - Schneider, Sebastian; Kerl, Hans Ulrich; Freundt, Miriam; Herrmann, Katrin Elisabeth; Groden, Christoph; Maros, Máté E.; Mohamed, Sherif A. (In vivo, 2025)
Background/Aim: Cervical selective nerve root block (CSNRB) is a widely used percutaneous procedure to diagnose and treat cervical radicular pain. The feasibility of a three-dimensional puncture planning and two-dimensional laser-guidance system has previously been shown in an ex vivo model. The purpose of this study was to further compare this technique to the conventional computed tomography (CT-)-guided approach. - Materials and Methods: Thirty CSNRBs were performed, each with Dyna-CT and the Syngo iGuide® laser-guidance system (Artis Zee® Ceiling, Siemens Medical Solutions, Erlangen, Germany), and with conventional CT-guidance (Somatom Volume Zoom, Siemens Healthcare, Erlangen, Germany) in an ex vivo lamb model. The number of puncture attempts, procedural planning time, puncture time, and trajectory length were evaluated and compared. - Results: All 60 punctures were rated as successful. Significantly less puncture attempts were needed with Dyna-CT compared to conventional CT-guidance (p<0.0001). Procedural planning time and puncture time were significantly shorter with Dyna-CT (pplan.t<0.0001 and ppunc.t=0.0004) (median 77 s and 56 s, respectively) than with conventional CT-guidance (median 109 s and 159.5 s, respectively), There were no significant differences in trajectory length (Dyna-CT median 3.18 cm; conventional CT median 3.33 cm, p=0.651). - Conclusion: Dyna-CT with Syngo iGuide® laser-guidance is superior to conventional CT-guidance for CSNRB in an ex vivo model. It significantly shortens the overall procedure time by reducing planning time, puncture time, and puncture attempts.
Online veröffentlicht: März 2025
Gesehen am 12.06.2025